What's your lockdown personality? - Kok, Li Xuan (Nanyang Technological University, 2022)
This project intends to explore the impacts of the pandemic on young adults aged 20 to 30 years old, as well as the comparisons in their lifestyles before and after covid. The rules and regulations have changed multiple times throughout, leaving young adults who are studying or working to adapt to the abrupt changes, some of which were delightful, while some unpleasant. Individuals have experienced advantages and disadvantages with these changes, generating mixed sentiments towards them. While finding out more data on this situation, I finalised 7 COVID-19 personalities people can relate to creating a participatory exhibition. This project intends for people to relate to the personalities, and share their heartfelt stories, while being able to read other people's stories, successfully evoking empathy among the youths.